Investigation on Fish Marketing System and Species Availability at Daulatpur Fish Market in Khulna, Bangladesh (Revised) (Journal of Environmental Science and Natural Resources, 2015)
16th February 2015. Due to a number of missing tables and figures, this article (DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22144) was withdrawn from Vol.7(1) and has been republished with corrections in Vol.7(2) pp.177-184 (DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22228).An investigation was carried out on the fish marketing system and availability of fish species at Daulatpur fish market in Khulna over 12-months from September 2012 to August 2013. Combinations of the participatory, qualitative and quantitative methods were used for questionnaire interviews for data collection. A total of 115 species of fresh water, brackish and marine water fish and crustacean species were identified during the observation period. The number of fresh water fish species was found 60 including 14 fresh water culture species and 12 SIS whereas brackish and marine water species was found 41 and crustacean species was 14 including 5 fresh water prawn, 6 marine and brackish water shrimp and 3 crabs. During the observation period, it was found that the availability of culture fish species was higher in the market and it was 55.86% including 17% catfish, 15.65 % tilapia, 15.56 % carp fishes, 4.18% koi, 2.47% punti and 1% prawn. Catfish, carps, tilapia, snakehead, baim, shing-magur, punti, koi etc were the major abundant groups among the fresh water fish species whereas ilish and some shrimp were the abundant species of marine and brackish water fish. The highest abundance (55.86%) was found the fresh water culture fish species following to marine and brackish water species (28.01%) and fresh water capture species (16.01%). The market chain from farmers/fishermen to consumers encompassed mainly primary, secondary and retail markets involving local agents (foria and bepari) suppliers, aratdars, wholesalers and retailers. During the observation, it was found that the auctioneers get 3 to 5% commission by performing their activities. Aratdars also get 4 to 5% commission due to arrange auctioning activities and providing other facilities such as clean water supply, electricity, space, communication etc which is called aratdary. In some cases farmers have to pay market tools that locally called khazna which vary from 5 to 10% depending on amount of sales. Market structure, species quality, size and weight have an influence on the price of fish and it was found that the price of fish increases per kilogram with increasing size and it varied with species to species. Every step of intermediaries of marketing channel obtained certain amount of profit and ultimately the farmers/fishermen received an average near about 60 percent of the retail price of fish in the market.DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22228 J. Environ. Sci. & Natural Resources, 7(2): 177-184 2014